Identification by PCR of non-typhoidal Salmonella enterica serovars associated with invasive infections among febrile patients in Mali. - Sharon M Tennant; Souleymane Diallo; Haim Levy; Sofie Livio; Samba O Sow; Milagritos Tapia; Patricia I Fields; Matthew Mikoleit; Boubou Tamboura; Karen L Kotloff; James P Nataro; James E Galen; et al. (Public Library of Science (PLoS), 2010)
In sub-Saharan Africa, non-typhoidal Salmonella (NTS) are emerging as a prominent cause of invasive disease (bacteremia and focal infections such as meningitis) in infants and young children. Importantly, including data from Mali, three serovars, Salmonella enterica serovar Typhimurium, Salmonella Enteritidis and Salmonella Dublin, account for the majority of non-typhoidal Salmonella isolated from these patients.We have extended a previously developed series of polymerase chain reactions (PCRs) based on O serogrouping and H typing to identify Salmonella Typhimurium and variants (mostly I 4,[5],12:i:-), Salmonella Enteritidis and Salmonella Dublin. We also designed primers to detect Salmonella Stanleyville, a serovar found in West Africa. Another PCR was used to differentiate diphasic Salmonella Typhimurium and monophasic Salmonella Typhimurium from other O serogroup B, H:i serovars. We used these PCRs to blind-test 327 Salmonella serogroup B and D isolates that were obtained from the blood cultures of febrile patients in Bamako, Mali.We have shown that when used in conjunction with our previously described O-serogrouping PCR, our PCRs are 100% sensitive and specific in identifying Salmonella Typhimurium and variants, Salmonella Enteritidis, Salmonella Dublin and Salmonella Stanleyville. When we attempted to differentiate 171 Salmonella Typhimurium (I 4,[ 5],12:i:1,2) strains from 52 monophasic Salmonella Typhimurium (I 4,[5],12:i:-) strains, we were able to correctly identify 170 of the Salmonella Typhimurium and 51 of the Salmonella I 4,[5],12:i:- strains.We have described a simple yet effective PCR method to support surveillance of the incidence of invasive disease caused by NTS in developing countries.